PENGELOLAAN ZIS DI UPZIS NU CARE-LAZISNU KECAMATAN SECANG KABUPATEN MAGELANG - Yeny Fitriyani; M Pudail; Tajun Yuhsinun; Ahmad Fauzan (STAI Syubbanul Wathon Magelang, 2021)
UPZIS NU Care-LAZISNU is a zakat managementinstitution formed by a community organization, Nahdlatul 'Ulama(NU), at the 31st Nahdlatul 'Ulama (NU) Muktamar in Boyolali in2004. This research aims to determine how the management systemzakat, infaq, and sadaqah funds use all organizational resources atUPZIS NU Care-LAZISNU. This study uses a qualitative method thatbegins by reviewing existing phenomena related to the managementof zakat, infaq, and sadaqah funds at UPZIS NU Care LAZISNU. Thetheory used in this study is the management theory put forward byA.F Stoner, who has described a theory of management. The results ofthis study indicate that the management of zakat, alms, and infaqfunds through comprehensive stages, starting from the fundraisingstage (fundraising), utilization and distribution, and reporting at UPZISNU Care-LAZISNU Secang District, has been going well.